2004
DOI: 10.1099/jmm.0.45685-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the escape of Francisella tularensis from the phagolysosome

Abstract: The highly virulent bacterium Francisella tularensis is well adapted to the intracellular habitat but the mechanisms behind its intracellular survival have been elusive. Recently, it was shown that the bacterium is capable of escaping from the phagosome of human and mouse monocytic cells. Here it is shown that this escape is affected by gamma interferon (IFN-ª) treatment of mouse peritoneal exudate cells since in treated cells the proportion that escaped was significantly lower (80 %) than in untreated cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(189 citation statements)
references
References 29 publications
11
177
1
Order By: Relevance
“…In order to evaluate the intracellular trafficking of the DpdpA mutant, we infected mouse macrophage-like cell line J774A.1 cells, and examined the co-localization of LAMP-1 with wild-type F. novicida, the DpdpA mutant, and a DiglC mutant. F. tularensis and F. novicida mutants in iglC have been shown by others to be defective for phagosome escape (Bonquist et al, 2008;Lindgren et al, 2004;Santic et al, 2005b). Our experimental results using deconvoluting fluorescence microscopy showed a clear separation of wild-type F. novicida and LAMP-1 localization at 12 h post-infection ( Fig.…”
Section: Lamp-1 Association Of the Pdpa Mutantsupporting
confidence: 50%
See 1 more Smart Citation
“…In order to evaluate the intracellular trafficking of the DpdpA mutant, we infected mouse macrophage-like cell line J774A.1 cells, and examined the co-localization of LAMP-1 with wild-type F. novicida, the DpdpA mutant, and a DiglC mutant. F. tularensis and F. novicida mutants in iglC have been shown by others to be defective for phagosome escape (Bonquist et al, 2008;Lindgren et al, 2004;Santic et al, 2005b). Our experimental results using deconvoluting fluorescence microscopy showed a clear separation of wild-type F. novicida and LAMP-1 localization at 12 h post-infection ( Fig.…”
Section: Lamp-1 Association Of the Pdpa Mutantsupporting
confidence: 50%
“…Other researchers have shown that mutation of some FPI genes leads to Francisella strains that fail to escape the phagosome (Bonquist et al, 2008;Lindgren et al, 2004;Santic et al, 2005b). Like this work, these studies are attempts to surmise the function of different FPI-encoded proteins by examining the intramacrophage phenotype of Francisella strains with lesions in FPI genes.…”
Section: Discussionmentioning
confidence: 99%
“…A gene (frgA; FTT0029) belonging to a family of hydroxamate-siderophore synthetic genes 33 was located downstream of fur, and a putative iron-box was found in the promoter region. Recent papers have described the ability of F. tularensis to escape the phagosome 34,35 . In the cytoplasmic environment, iron is highly insoluble, and a TonB-dependent system for complex-bound iron uptake would be expected.…”
Section: Virulence and Iron Acquisitionmentioning
confidence: 99%
“…9,10 Deletion of a genetic locus, the Francisella Pathogenicity Island (FPI), abolishes the ability of F. tularensis to escape into the host cytosol. 11,12 The DFPI mutant remains in a vacuolar compartment, is unable to replicate intracellularly and is highly attenuated in vivo.…”
mentioning
confidence: 99%